ANALISIS KELAYAKAN FINANSIAL DAN LINGKUNGAN INDUSTRI TERHADAP PEMBANGUNAN SARANA RETEST, REPAIR DAN REPAINT TABUNG GAS LPG 3KG (STUDI KASUS PT MK TABANAN, BALI) - Utomo, Slamet Sucahyo; Fadah, Isti; Puspitasari, Novi (JURNAL EKONOMI AKUNTANSI DAN MANAJEMEN, 2014)
High level of confidence required in an investment planning. This is an important according to the accuracy of the strategic policy choices before an investment project to be executed. Appropriate recommendations are derived from the financial assessment (quantitative) and non-financial (qualitative) are expected to provide appropriate recommendations to the investment plan. This study was conducted to determine the feasibility of construction of infrastructure investment retest, repair and repaint 3kg LPG gas cylinders in terms of the financial aspects of investment models approach the Net Present Value (NPV), (2) Internal Rate of Return (IRR), (3) Payback Period (PP), (4) Profitability Index (PI) and non-financial aspects of the environmental analysis of the industry using Porters 5 Forces approach Keywords: Project Investment, NPV, IRR, PP, PI, Porter 5 Forces